The ecological community and the solidarity link between men. (Nóema, 2022)
To overcome problems related to nature it’s necessary to understand how they derive from society. Contemporary society is characterized by the domination of man over man from which the conviction of the enslavement of nature derives. This condition is determined by capitalism, the last form of hierarchy and domain. The ego, in this situation, became strengthen incapable to encounter the Other and to relate to him. It follows from that the I needs to overcome the solipsism where the individual is locked up the I-Thou relationship that takes place in the community. The perennial production and constant consumption also irremediably mark the relationship between men and nature. The possible solution derives, as Ivan Illich proposes, from the conviviality that can be achieved only by placing limits on production. The transition to a convivial society allows to strengthen the community bond and the recognition of the symbiotic relationship with nature.
Keywords: Ecology; community; relationship; capitalism; conviviality; tool; hierarchy; dominion; utopia